Improving competitiveness of economic entities hotel business - O. V. Babich; E. A. Tarasova (Путеводитель предпринимателя, 2020)
This article deals with the problem of increasing the competitiveness of Russian enterprises of the hotel business. The relevance of the chosen topic is justified by the increased level of competition in the considered market, changes in the state policy in the field of hotel business, and the growth of consumer demand for hotel services.